A Review of Policies to Reduce Waiting Times for Health Services across OECD Countries - Luigi Siciliani (University of Oslo, 2023)
Waiting times for health services are a significant policy issue in most OECD countries, where improving the experience and patient satisfaction with the health system is a key objective. Waiting times in publicly-funded systems arise from the imbalance between demand for and supply of health services. This study reviews policies aimed at reducing waiting times in OECD countries across different health services: specialist consultations and elective treatments; consultations with primary care providers; cancer care; and mental health services. A policy questionnaire was sent by the OECD in May 2019. For each area it asked information on a) policies, its objectives and actions, b) the extent to which they were regularly evaluated or assessed, and c) main results of the evaluation. 33 countries provided at least a partial response, with 24 countries providing detailed information about the policies, which are reviewed in this study. Our key findings are as follows. Countries often start by specifying maximum waiting times across a range of services, which can be used as a guarantee for patients and/or targets for providers. Policies for elective care include improving demand management by prioritising patients on the list, and improving coordination between primary and secondary care. For primary care, policies focus on increasing the supply of general practitioners and advanced practice nurses, and encouraging the use of new technologies (e.g. teleconsultations). For cancer care, countries have developed national strategies to ensure timely access to diagnosis and treatment, including fast-track pathways, which rationalise and coordinate different types of cancer services, facilitated by dedicated capacity. Policies for mental health focus on better meeting demand through increased volume or scope with, in some cases, targets driving better access. In summary, policymakers have several levers to reduce waiting times along the patient pathway to improve responsiveness and make health systems more people centred.